144k views
4 votes
Can anyone answer this ?

plz show your working as well
1) (3x2– 4x – 1) + (8x2– x + 6)
2) (6x2– x – 4) + (2x2+ 5x – 5)
3) (4x2 +2x – 5) + (6x2– x – 5)

1 Answer

3 votes

1.


(3 {x}^(2) - 4x - 1) + (8 {x}^(2) - x + 6) \\ \\ combining \: the \: like \: terms,\:we\:have\\ \\ = 3 {x}^(2) + 8 {x}^(2) - 4x - x - 1 + 6 \\ \\ = 11 {x}^(2) - 5x + 5

2.


(6 {x}^(2) - x - 4) + ( 2{x}^(2) + 5x - 5) \\ \\combining \: the \: like \: terms, \: we \: have \\ \\= 6 {x}^(2) + 2 {x}^(2) - x + 5x - 4 - 5 \\ \\= 8 {x}^(2) + 4x - 9

3.


(4 {x}^(2) + 2x - 5) + (6 {x}^(2) - x - 5) \\ \\ combining \: th e\:l ike \: terms, \: we \: have \\ \\= 4 {x}^(2) + 6 {x}^(2) + 2x - x - 5 - 5 \\ \\= 10 {x}^(2) +x - 10


\large\mathfrak{{\pmb{\underline{\orange{Happy\:learning }}{\orange{.}}}}}

User Klim
by
5.4k points